Evaluasi dan Pengembangan Sistem Laporan Stok Barang Menggunakan Enterprise Resource Planning (ERP) - Arif Prayogi; Noviandi Noviandi (Universitas Wahid Hasyim, 2024)
Stock or inventory is crucial for the company because stock availability will determine the continuity of the transaction to be carried out. At PT. Citra Prima Kharisma, the reporting system is still manual using Microsoft Excel and stock cards, so stock reports are often inaccurate and real-time. This study aims to develop a reporting system with an ERP concept that integrates the sales department with the warehouse department so that the resulting stock reports are accurate and can be viewed in real-time. The system development methodology is used by applying the ERP implementation methodology, where methodology consists of the initial stage, the analysis phase, the construction phase, and the operational phase. This research produces an ERP-based reporting system that integrates data from each department, allows direct data exchange and ensures the consistency and accuracy of information. This system is able to present information in real time and produce accurate reports according to the quantity and condition of goods. This provides significant advantages in stock management and increases the operational efficiency of the company. System testing using SUS showed good acceptance with a score of 75.75 indicating a good level of acceptance of system quality and performance.